Rules for Radical Lawyers: Advancing the Abortion Rights of Inmates - Egerman, Mark (Columbia Journal of Gender and Law, 2011)
William Lloyd Garrison famously declared that the Constitution was a covenant with the devil – and then proceeded to bum a copy. I For a radical abolitionist like Garrison, the statement was an accurate description of the Constitution’s origins because, as every civics student knows, the Constitution reflects a process of compromise between slave states and free states that affected multiple aspects of the document, most explicitly the three-fifths compromise. Garrison’s statement was more than a description of the process of compromise; he was also promulgating his view, one that distinguished him from other abolitionists of his era, on how slavery could be defeated. Garrison, like Wendell Phillips, saw the Constitution as part of the slavery problem and not as part of the abolitionist solution. Others, such as Frederick Douglass and Lysander Spooner, believed it possible to use constitutional arguments to eradicate slavery. To these constitutional abolitionists, the document could be read to support an abolitionist argument, and these abolitionists reasoned that it was a mistake to assume that the Founding Fathers had intended to institutionalize slavery forever. Putting aside the merits of the respective arguments, Garrison’s view would ultimately prevail. The legal and governmental structures founded on the Constitution were unable to peacefully abolish slavery and the country ultimately went to war to resolve the issue.